Cellular predation and motility as drivers of animal origins and the Cambrian radiation - Zhang, Luwen (Frontiers in Ecology and Evolution, 2026)
The Cambrian radiation (~539 Ma) generated most animal body plans in ~20 million years. This rapid diversification raises the central question of how genomic innovation for architectural change—rather than merely multicellularity—arose in early animals. We propose that cellular predator–prey interactions among single-celled ancestors, together with motility evolution, drove early genomic change. Failed predation attempts—where prey escaped or predators suffered cellular damage—exposed cells to oxidative and enzymatic stress, triggering error-prone DNA repair and transposable-element activation that produced chromosomal rearrangements including Hox cluster reorganization, regulatory network rewiring, and gene duplications—changes with direct consequences for segmentation, symmetry, and appendage architecture. Motility served as an evolutionary filter: highly motile cells evaded recurrent engulfment, whereas low-motility cells repeatedly experienced predation-induced genomic stress and accumulated heritable variants. Phagocytosis expanded within eukaryotes during the Neoproterozoic, aligning with early animal evolution. The Cambrian “Goldilocks” window—rising oxygen, elevated resources, and low ecological incumbency—both accelerated architectural variant generation and created ecological space for body-plan innovations to persist and elaborate. Our model addresses both multicellularity achievement and subsequent phylum-level architectural diversification, proposing that predation-driven genomic stress generated the substrates later expressed as distinct tissues, axes, and organ systems. This framework accounts for the magnitude, timing, and uniqueness of animal origins while generating testable predictions linking cellular-stress signatures with genomic patterns in early-branching animals.